2010
DOI: 10.1682/jrrd.2010.01.0003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prosthetic foot forefoot flexibility on oxygen cost and subjective preference rankings of unilateral transtibial prosthesis users

Abstract: Abstract-The investigators conducted a double-blind randomized crossover study to determine the effects of prosthetic foot forefoot flexibility on oxygen cost and subjective preference rankings of 13 unilateral transtibial prosthesis users. Five experimental feet were fabricated for use in the study: F1, F2, F3, F4, and F5. F1 was most flexible, F5 was least flexible, and F3 was designed to conform to a biomimetic ankle-foot rollover shape. The experimental feet were modeled after the Shape&Roll prosthetic foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 15 publications
(23 reference statements)
0
48
3
Order By: Relevance
“…Following selection for relevance and including those resulting from the secondary search, we identified 36 articles that satisfied the criteria [2][3][5][6][7][13][14][15][16][17][18][19][20][21][22]. In addition, five relevant review articles were identified [1,[8][9][11][12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following selection for relevance and including those resulting from the secondary search, we identified 36 articles that satisfied the criteria [2][3][5][6][7][13][14][15][16][17][18][19][20][21][22]. In addition, five relevant review articles were identified [1,[8][9][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…As a follow-up to the this study, two additional studies by Klodd et al also used the "Shape&Roll" prosthetic foot in order to study the effects of forefoot roll-over shape on gait kinematics, kinetics, and oxygen cost [21][22]. Changes to forefoot roll-over shape were achieved in a foot of the same length by increasing the number of cutouts made in the dorsal aspect of the forefoot.…”
Section: Combined In Vivo and Aipp Characterization Studies That Havementioning
confidence: 99%
See 2 more Smart Citations
“…As suggested in another study [30], the cuts might have been too close together to function as intended. Future work should investigate a different approach to modulation of forefoot stiffness, such as deepening or widening the cuts.…”
Section: Limitationsmentioning
confidence: 97%